Streams to the river, river to the sea : a novel of Sacagawea - O'Dell, Scott, 1898-1989 (Houghton Mifflin, 1986)
A young Indian woman, accompanied by her infant and cruel husband, experiences joy and heartbreak when she joins the Lewis and Clark Expedition seeking a way to the Pacific.